Vascular changes in the retina in patients with chronic respiratory insufficiency - Adžić-Zečević, Antoaneta; Milojko, Biljana; Janićijević-Petrović, Mirjana A. (Vojnosanitetski pregled, 2014)
Background/Aim. Chronic respiratory insufficiency is a pathological state which occurs as a result of respiratory system inability to maintain normal gas exchange between the outside air and circulating blood. For the purposes of human organism’s proper functioning, it is necessary that a certain amount of air in the lungs comes into contact with a certain amount of blood within a unit of time, so that an adequate hemoglobin oxygenation could be achieved. Then, hemoglobin from erythrocytes in the blood supply delivers oxygen to all the tissues and cells of the body including the eye. Direct impact of hypoxemia and hypercapnia on the wall of arterioles, venules and capillaries results in a severe vasodilatation along with the increased permeability of the walls causing clinically evident changes in the retina. The aim of this study was to determine the degree of ocular changes in retina with patients suffering from chronic respiratory insufficiency. Methods. A prospective study was conducted on 80 patients, 40 patients with respiratory failure and 40 patients with chronic obstructive pulmonary disease an and bronchial asthma (the control group). In all the patients direct and indirect ophthalmoscopy and fluoresceine angiography was performed. Clinically visible fundus and retina changes in patients suffering from chronic respiratory failure were categorized as mild (dilatation and retinal veins and arteries tortosion up to the mid-periphery), moderate (retinal hemorrhage) and severe (optic nerve edema, macular edema, superficial and deep retinal hemorrhages and venous occlusion). Results. In the patients suffering from respiratory insufficiency the changes in retinal blood vessels were found [in 18 (45%) mild, in 13 (32.5%) moderate, and in 9 (22%) severe], while in the patients with chronic obstructive pulmonary disease and bronchial asthma (without respiratory insufficiency) no changes were recognized. Conclusion. The results of this study indicate the need for ophthalmologic examination in patients with chronic respiratory insufficiency. It is important to recognize, identify and quantify the changes on retinal blood vessels which are clinically significant. It is necessary to provide their monitoring and to prescribe proper therapeutic treatment in order to preserve visual functions.
Keywords: respiratory insufficiency; pulmonary disease; chronic obstructive; anoxia; retinal disease; optic nerve